Tourism Recovery Policies from Covid 19 Pandemic Case of the First Destination in the World France - Ali, Amel Brahim; Belahcene, Bilal (جامعة علي لونيسي البليدة 2 - كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2024)
The aim of our study is to present the impact of unprecedented spread of Covid 19 in the beginning of 2020 on tourism sector. Hence, we Compared tourism performance indicators pre and post the health crisis, then we discussed the measures which gathered by France Government to recover tourism sector. we concluded that the first destination in the world allocated a budget of more than 38 billion euro divided into five axis that allow France to recover rapidly and preserve its international rank.
Keywords: التنمية السياحية -- الأزمات الصحية -- جائحة كورونا "كوفيد-19"